Physical characterization of electrospun polycaprolactone via laser micrometry: Porosity and condition-dependent jet instabilities. (21st December 2020) - Liu, Y.; Fan, F.; Dull, T.; Chaparro, F.J.; Franz, C.S.; Abdalbaqi, A.; McElroy, C.A.; Lannutti, J.J.
Abstract: Electrospinning has acquired intense recent interest as a means of advancing filtration, tissue engineering, and catalysis. As a part of this evolution, better characterization of electrospinning conditions has been identified as a variable that can improve performance. We use a unique realization of laser micrometry to reveal previously unknown porosity trends within electrospun poly(ε-caprolactone) (PCL) deposited onto a cylindrical mandrel. Electrostatic charging of two PCL-based solutions took place in N2 at 0 and 50%RH under three collector biases (−5, 0, and +5 kV). At 0%RH, all three gave rise to porosity values of 85–95%, where 95% occurred at the edges of +5 kV; mid-point values were a relatively constant 86–90%. Increases to 50%RH at –5 kV caused edge porosity values of ~56%; mid-point values were ~91% due to a well-defined 'texture.' The addition of higher dielectric constant Rose Bengal (RB) caused minor porosity changes at 0%RH, but dramatic changes at 50%RH; mid-points were as low as 12%; edge values reached >80% before decreasing to ~60%. Dense fiber agglomerations were present due to RB's effect on surface charge migration and decreased fiber repulsion along with deposit relaxation likely due to increased solvent retention. Multi-needle depositions of separate PCL and PCL-RB solutions at 0%RH produced a visually uniform, ~90% porous deposition. However, RB analysis showed separated contributions containing either RB-rich or RB-poor fibers. At 50%RH, midpoint porosities decreased to 0% and similar RB-poor or RB-rich regions occurred where 0% was associated with RB likely due to jet segregation due to differences in the grounding ability of PCL versus PCL-RB solutions. This analysis captures variations in through-thickness porosity to provide unprecedented detail regarding conditional effects on electrospun products. Graphical abstract: Image 1 Highlights: Quantitative mapping of porosity across electrospun depositions is a strong technological need. Laser micrometry provides a robust technique characterizing electrospun porosity variations. Humidity changes can produce up to 89% variation in porosity. Two-needle depositions can produce non-uniform compositional profiles and 0% porosity.